Undergraduate Students’ Perception of Using Extensive Reading Strategy in Vocabulary Mastery - Zelvia Dina Octavianti; Pratiwi Retnaningdyah; Ahmad Munir (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: Reading is one of the most essential skills in learning, especially in English learning. Technological sophistication that is developing rapidly in the 21st century requires students to be literate in order to be able to compete in critical thinking and receive the latest information. The program suitable for the conditions of students in this century is extensive reading, which offers reading for pleasure according to the level of students' abilities. Method: The type of approach used in this research is qualitative. Only fifteen undergraduate students have received an extensive reading course in the fifth semester to obtain optimal results. In collecting data using two instruments, namely questionnaires and interviews. Results: The results shown in this research are that most undergraduate students have positive perceptions after receiving extensive reading course program activities, one of which is the addition of vocabulary that affects their reading motivation. Novelty: The results of this research encourage future researchers to dig up information about the effectiveness of using extensive reading in increasing vocabulary acquisition.